How to be a Better Plea Bargainer - Cynthia Alkon; Andrea Kupfer Schneider (Washington University Journal of Law & Policy, 2021)
Preparation matters in negotiation. While plea bargaining is a criminal lawyer’s primary activity, the value of this skill is discounted by law schools and training programs. A systemic model can be used to improve plea bargaining skills. This Article offers a prep sheet for both prosecutors and defense attorneys and explains how each element of the sheet specifically applies to the plea bargaining context. The prep sheet is designed as a learning tool so that the negotiator can learn from the sheet and then make their own. The sheet highlights important considerations such as understanding the interests and goals of the parties, the facts of the case, the law, policies behind the law, elements of an agreement, how to communicate with the other parties, and more. The serious power imbalances and constraints inherent in the plea bargaining process make preparation crucial. Alkon and Schneider urge lawyers, scholars, and clinicians to become part of the ongoing conversation so that the practice of law can be improved for the benefit of all.
Keywords: plea; plea bargain; plea bargainer; plea bargaining; negotiate; negotiation; legal education; criminal law